Ensino instrumental na escola básica e sua aplicação na U. E. B. Gomes de Sousa, São Luís-MA - Santos, Daniel Ferreira (2016)
This study aimed to analyzing the application of a teaching methodology based on musical instruments practices in U.E.B. Gomes de Sousa school. This institution is located in the suburb of Sao Luis named as Vila Maranhão. The methodology is characterized as a complementary way to the music art teaching and learning process of the students enrolled in the final levels of the elementary school. Moreover, its contributions on the thinking about the applicability and importance of instrumental teaching as well as its capability to offer a vision of how musical education and instrumental practices can integrate the curriculum of the basic education were taken in account. For a better comprehension regarding to the reality of this method, it was conducted a profound research on the instrumental music teaching programs adopted in other countries educational systems. To improve the practice used here, the methodology used by teachers and teaching strategies that can be consistent and enrich the approach of this research were analyzed. Among them, it could be mentioned the Suzuki philosophy, the fundamental learning theory based on Edwin Gordon, and the usage of the teaching collective method tools knows as orchestra Da Capo Tutti from Prof. Dr. Joel Barbosa. As the main methodological procedure in order to carrying out this research work, it was done a kind of research-action. This aimed to make links between theory and practice on the application of instrumental project onset practices by investigating their contributions and results on the educational, social and political outcomes for the area of instrumental music education. The results achieved allowed to perceive the challenges on the issues about the curriculum concepts and implementation of instrumental training programs to provide a complementary background to the students enrolled in the basic education system. Furthermore, the results enable to evaluate the significant gains during the construction process of various diversity ways to be followed in the music learning. To sum up, through all the research carried out and pedagogical suggestions, it was possible to confirm that the instrumental teaching process applied to the elementary school acted as a strengthening way to consolidate the music teaching in this context. Moreover, was observed a natural interest in musical art from the part of youth people and comprehensiveness that this practice offers. Finally, this practice serves as a model of idealization for an effectiveness way to implement musical instruments teaching routine in all Brazilian schools.